AutoCAD & AutoCAD LT all-in-one - Ambrosius, Lee (--For dummies., 2026)
"In the brand-new second edition of AutoCAD & AutoCAD LT All-in-One For Dummies, consultant and industry expert with more than 30 years of experience using and extending AutoCAD along with being a 20-year veteran of AutoCAD education, Lee Ambrosius, walks you through the fundamentals of AutoCAD and AutoCAD LT. He explains the most useful features of both AutoCAD and the more budget-friendly AutoCAD LT, showing you how to choose the right tools and workflows for your projects." --